2013
DOI: 10.1590/s1679-45082013000100014
|View full text |Cite
|
Sign up to set email alerts
|

Padronização de modelo experimental adequado a estudos do efeito do exercício na artrite

Abstract: Objective:To standardize an experimental model of chronic monoarthritis induced by complete Freund's adjuvant appropriate for the analysis of the effect of walking on nociception and on joint edema.Methods:The following factors were evaluated as to monoarthritis induction: route and site of administration, number and interval of inoculations, Mycobacterium species, and animal gender. Wistar male and female rats (200 to 250g) received two injections of complete Freund's adjuvant containing Mycobacterium tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…In the first phase, edema rate of the injected footpad increased and reached a peak during the first 3 days. Thereafter, the swelling slowly subsided until the seventh day when the paw began to swell again and peaked in the second week (second phase); this effect of increasing edema (increase in inflammatory mediators) after 7 days of CFA injection has already been reported by other researchers (Gomes et al 2013). The administration of the aqueous fraction (5 mg/kg) inhibited the development of joint swelling induced by CFA (51.39%) when compared to the 5 mg/kg IND-positive control (63.19%) on the eighth day after CFA injection (Fig.…”
Section: Effect On the Inflammatory Parameterssupporting
confidence: 70%
“…In the first phase, edema rate of the injected footpad increased and reached a peak during the first 3 days. Thereafter, the swelling slowly subsided until the seventh day when the paw began to swell again and peaked in the second week (second phase); this effect of increasing edema (increase in inflammatory mediators) after 7 days of CFA injection has already been reported by other researchers (Gomes et al 2013). The administration of the aqueous fraction (5 mg/kg) inhibited the development of joint swelling induced by CFA (51.39%) when compared to the 5 mg/kg IND-positive control (63.19%) on the eighth day after CFA injection (Fig.…”
Section: Effect On the Inflammatory Parameterssupporting
confidence: 70%
“… 2 , 3 RA may possibly progress to severe disability with direct negative impacts on life style and increase in mortality rate. 4 , 5 The overall prevalence of clinically diagnosed RA was 0.5–2% of the population with higher prevalence in developed countries. 6 All ages are susceptible to develop RA, but the incidence increased significantly in people aged over 40 years, especially women who are two to three times more susceptible to RA than men.…”
Section: Introductionmentioning
confidence: 99%
“…of motion, and flexibility, decrease pain, improve gait (Kapale et al, 2017;Shih et al, 2006), increase muscle mass, reduce adiposity, and improve muscle strength, physical fitness, fatigue, psychological well-being, and overall life quality (Mcinnes & Schett, 2011). Gomes et al (2013) reported that physical exercise could reduce edema and leukocyte migration in animals with CFA-induced arthritis. Evidence suggests that activity can be performed as soon as the RA diagnosis with no joint damage is confirmed.…”
Section: Discussionmentioning
confidence: 99%